2013
DOI: 10.1128/iai.01043-12
|View full text |Cite
|
Sign up to set email alerts
|

The B Subunit of an AB5 Toxin Produced by Salmonella enterica Serovar Typhi Up-Regulates Chemokines, Cytokines, and Adhesion Molecules in Human Macrophage, Colonic Epithelial, and Brain Microvascular Endothelial Cell Lines

Abstract: bThe principal function of bacterial AB5 toxin B subunits is to interact with glycan receptors on the surfaces of target cells and mediate the internalization of holotoxin. However, B subunit-receptor interactions also have the potential to impact cell signaling pathways and, in so doing, contribute to pathogenesis independently of the catalytic (toxic) A subunits. Various Salmonella enterica serovars, including Salmonella enterica serovar Typhi, encode an AB5 toxin (ArtAB), the A subunit of which is an ADPrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…At present, the role of ArtAB in the pathogenesis of salmonellosis remains obscure, apart from its role as a delivery vehicle for CdtB in S. Typhi (10). However, in addition to the vacuolation phenotype reported in this study, we have shown that similar concentrations of ArtB trigger the secretion of chemokines, proinflammatory cytokines, and adhesion molecules in diverse cell types (12). Thus, ArtB may also contribute to pathogenesis independently of the A subunit by promoting and maintaining a strong inflammatory response at the site of infection as well as by inducing vacuolation.…”
Section: Figmentioning
confidence: 60%
See 2 more Smart Citations
“…At present, the role of ArtAB in the pathogenesis of salmonellosis remains obscure, apart from its role as a delivery vehicle for CdtB in S. Typhi (10). However, in addition to the vacuolation phenotype reported in this study, we have shown that similar concentrations of ArtB trigger the secretion of chemokines, proinflammatory cytokines, and adhesion molecules in diverse cell types (12). Thus, ArtB may also contribute to pathogenesis independently of the A subunit by promoting and maintaining a strong inflammatory response at the site of infection as well as by inducing vacuolation.…”
Section: Figmentioning
confidence: 60%
“…using Ni-nitrilotriacetic acid (NTA) chromatography, as previously described (12). Where required, proteins were fluorescently labeled by using a DyLight 488 antibody labeling kit (Thermo Scientific) according to the manufacturer's instructions.…”
Section: Fig 11mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are most likely attributable to signaling events triggered by interactions of the mutant toxin's B-subunit pentamer with receptors on the target cell surface. Indeed, we recently showed that ArtB, a homologue with ϳ50% identity to SubB produced by Salmonella enterica serovar Typhi, upregulates a range of chemokines, cytokines, and adhesion molecules in the same cell lines used in the present study (23). Thus, the A and B subunits of SubAB may have distinct, perhaps even opposing effects on chemokine and cytokine responses during infection with SubAB-producing STEC.…”
Section: Discussionmentioning
confidence: 90%
“…The examined proinflammatory cytokines were TNF-␣ and IL-6. Secreted chemokines and cytokines in cell culture supernatants were assayed using cytometric bead array kits (Bender Medsystems) according to the manufacturer's instructions, as described elsewhere (23). During incubation of the beads with culture supernatant, different analytes were captured by their corresponding beads.…”
Section: Methodsmentioning
confidence: 99%